Neuropathic Pain Therapy: From Bench to Bedside - Backonja, Miroslav Misha (Seminars in Neurology, 2012)
Neuropathic pain is a result of complex interactions between peripheral and central mechanisms with multiple potential therapeutic targets. However, the complexity of these mechanisms and relative youth of translational pain research, which is in its infancy, have prevented translation of successful basic bench research to human therapy. Most of the clinically available neuropathic pain treatments are borrowed from other therapeutic areas, such as antidepressants and antiepileptics, or involve application of older therapy, such as opioids. Exceptions are ziconotide, tapentadol, and the high-concentration capsaicin patch. Similar to all other analgesic agents, these provide only partial pain relief in subsets of patients. The standard of care for patients with chronic neuropathic pain is multimodal and multidisciplinary. For most patients to achieve and maintain satisfactory pain relief a combination of therapeutic agents is necessary, providing the empiric basis for rational polypharmacy, which has become a standard approach as well.
Keywords: neuropathic pain; somatosensory nervous system; mechanisms of action; analgesia